Pengembangan Perangkat Pembelajaran Menggunakan Model Problem Based Learning - Sri Mardayani; Syahril Syahril; Fahmi Rizal (Universitas Negeri Padang, 2019)
This study aims to develop learning tools Health Safety and Environment using problem based learning model in meeting the demands of the revised 2013 edition curriculum. This research is a research and development (R & D) with ADDIE model which consists of Analyze, Design, Development, Implementation, and Evaluation stage. The developed tools consist of syllabus, Learning Implementation Plan (RPP), Student Work Sheet (LKPD), and assessment. The results showed that the products developed in the criteria are very valid on the aspects of validity, the criteria are very practical on the aspects of practicality, and the criteria are on aspects of effectiveness. it can be concluded that the learning device Health Safety and Environment using problem based learning model has met the valid, practical, and effective criteria.